2021
DOI: 10.3390/genes12030451
|View full text |Cite
|
Sign up to set email alerts
|

The Conservation of Low Complexity Regions in Bacterial Proteins Depends on the Pathogenicity of the Strain and Subcellular Location of the Protein

Abstract: Low complexity regions (LCRs) in proteins are characterized by amino acid frequencies that differ from the average. These regions evolve faster and tend to be less conserved between homologs than globular domains. They are not common in bacteria, as compared to their prevalence in eukaryotes. Studying their conservation could help provide hypotheses about their function. To obtain the appropriate evolutionary focus for this rapidly evolving feature, here we study the conservation of LCRs in bacterial strains a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…In terms of function, for bacteria, Peng et al [ 51 ] identified a correlation between intrinsically disordered regions and DNA and RNA binding, as well as sporulation, catabolic and metabolic processes, and pathogenesis. Mier et al [ 54 ] also suggest that LCR are more represented in the outer membrane and extracellular proteins in bacteria, being involved in host–pathogen interactions. These discoveries unravel the importance of disorder and LCR in proteins associated with pathogenicity and adhesion processes, encouraging further study of the importance of these domains in CLPs.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of function, for bacteria, Peng et al [ 51 ] identified a correlation between intrinsically disordered regions and DNA and RNA binding, as well as sporulation, catabolic and metabolic processes, and pathogenesis. Mier et al [ 54 ] also suggest that LCR are more represented in the outer membrane and extracellular proteins in bacteria, being involved in host–pathogen interactions. These discoveries unravel the importance of disorder and LCR in proteins associated with pathogenicity and adhesion processes, encouraging further study of the importance of these domains in CLPs.…”
Section: Resultsmentioning
confidence: 99%
“…An LCR motif found across species may be crucial in host-pathogen interactions, or it may perform an endogenous function common in both organisms and not part of the interactions between pathogen and host. Given their functional importance alongside their role in hostpathogen interactions [52,53] and that mutation rates increase with proximity to LCRs [54][55][56][57][58], it is likely that host regulatory LCRs are mimicked by pathogens. However, it is incredibly challenging to identify the function of an LCR.…”
Section: Discussionmentioning
confidence: 99%
“…Resolution of these low-complexity regions (LCRs) has been a challenge for many sequencing platforms, and has limited the adoption of nanopore sequencing for widespread HPAIV genomic surveillance 20 . Accurately sequencing LCRs is important for many pathogens relevant to human and animal health [30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%